Use of artificial saliva for instrumental evaluation of the texture of expanded snacks: part I—mechanical and acoustic properties - Guazi, Julaísa Scarpin [UNESP]; Conti, Ana Carolina [UNESP] (Springer Nature, 2023)
The texture analyzer is the equipment most used to measure the texture properties of foods, although it has limitations in reproducing some conditions of the oral cavity such as temperature and sample moisturizing by human saliva. Thus, this study uses artificial saliva during analysis with a texture analyzer, having expanded snacks as the case-study and using different probes. Thirteen samples of expanded snacks were analyzed using seven probes and three different treatments: with no saliva, with 1.1 mL of artificial saliva applied to the sample and immersion of the sample in the artificial saliva. Force (highest force peak, number of force peaks, average of maximum force and adhesiveness) and acoustic properties (number of acoustic peaks and sound pressure level) were measured. In general, there was a reduction in the values of the instrumental texture properties from the samples without artificial saliva compared to those with artificial saliva applied and, even more so, compared to the samples immersed in the artificial saliva. Nevertheless, different behaviors were found between some samples and between the probes. Which concerns the treatments with artificial saliva, each one has advantages and difficulties in terms of testing performance, absorption by the sample and wasting. In conclusion, we suggest cylindrical and three-point bending probes to evaluate the texture of expanded snacks, because of their discrimination of texture properties and ease of operation.
Keywords: Acoustic properties; Artificial saliva; Expanded snacks; Force properties; Texture analyzer